Publicists in US Public Relations History: An Analysis of the Representations of Publicists, 1815–1918. Issue 1 (2nd January 2017) - Myers, Cayce
Abstract : The role of publicists in public relations history is largely overlooked. Although today publicists are commonly associated with the entertainment industry, late nineteenth and early twentieth century publicists were a professional group that played an important role in developing modern public relations practice, particularly the craft of research-based, ethical, and strategic communication. These early publicists' reputations and skills at managing public opinion were highly sought after by universities, businesses, and in political circles. Because their work often involved international issues, their impact was present both domestically and outside of the United States. Understanding the role the publicist played in public relations development presents a new narrative of public relations history that shows that early public relations practice contained professional, strategic, and international communication practices.